Loosening state controls in Singapore: the emergence of local capital as a political force - Chalmers, Ian (Ashgate Publishing, 2001)
There has been a diminution in state capacity to control social forces in Singapore as rapid economic growth during the last two decades has created sizeable middle and capitalist classes. State autonomy from social pressure has declined, and processes of class formation are increasingly changing state corporatist institutions. The politics of business development policy indicates that the `consultative decision-making' of the mid-1980s was initially a response to international economic developments. However, the national business class has since become more politically influential. The Singapore state has become susceptible to pressure group activity more generally, increasing strains on its dominant ideology of dirigisme.